Терракотовые сестры: [роман] / Мила Коротич - Коротич Мила (Ник Перумов, 2013)
Экземпляры: Узинская библиотека (20151030) / Инвентарный номер: 202347 / Цена: 172.81 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 68 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6